Helping coaches apply the principles of representative learning design: validation of a tennis specific practice assessment tool. Issue 11 (3rd June 2018) - Krause, Lyndon; Farrow, Damian; Reid, Machar; Buszard, Tim; Pinder, Ross
ABSTRACT: Representative Learning Design (RLD) is a framework for assessing the degree to which experimental or practice tasks simulate key aspects of specific performance environments (i.e. competition). The key premise being that when practice replicates the performance environment, skills are more likely to transfer. In applied situations, however, there is currently no simple or quick method for coaches to assess the key concepts of RLD (e.g. during on-court tasks). The aim of this study was to develop a tool for coaches to efficiently assess practice task design in tennis. A consensus-based tool was developed using a 4-round Delphi process with 10 academic and 13 tennis-coaching experts. Expert consensus was reached for the inclusion of seven items, each consisting of two sub-questions related to (i) the task goal and (ii) the relevance of the task to competition performance. The Representative Practice Assessment Tool (RPAT) is proposed for use in assessing and enhancing practice task designs in tennis to increase the functional coupling between information and movement, and to maximise the potential for skill transfer to competition contexts.